Several Notes on Engraved Gems from Southern Pannonia - Kaić, Iva (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
Engraved gems from Eastern Pannonia are well known thanks to the scholarly work of professor Tamás Gesztelyi on the gems from Brigetio, Acquincum, Intercissa and Gorsium. Carnuntum in Western Pannonia yielded more than 1300 engraved gems, thus outnumbering all other findspots in the Province. In order to further complement the topography of gem findspots in Pannonia, this paper provides a brief conspectus of the engraved gems from Siscia in Southern Pannonia.